Building a Restaurant-Specific Sentiment Lexicon via Probability Theory - Melo, Tiago de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2021)
Online user reviews written in Portuguese language are widely used by native speakers from several countries for decision-making and a large amount user reviews are available on the Web. However, only few studies on Portuguese sentiment analysis are reported as there is a lack of resources including domain-specific sentiment lexical collections. In this paper, we present an effective method for building a set of lexicons in restaurant domain for Portuguese language. The experiments on a large data collection of user reviews illustrate that our method significantly outperforms several alternative previous approaches of building domain-specific sentiment lexicon.